RISK FACTORS AND PREDICTION OF PERINATAL LESIONS OF CNS IN NEWBORNS IN ANTENATAL PERIOD OF DEVELOPMENT - O.B. Chernyakhovskiy; O.L. Polyanchikova ("Paediatrician" Publishers LLC, 2008)
Frequency, structure and consequence of different risk factors of intra ventricular bleeding in newborns are presented in this article. This data was obtained from results of statistical and correlation analysis of information from delivery cards of women with risk factors, resulting in fetal hypoxia and lesion of CNS in newborn. These risk factors were discovered in women at the time of registration in antenatal clinic because of pregnancy and at the period of gestational process. prediction of risk rate of pathology onset was calculated with method of normalized intense indices. Key words: newborns, perinatal cns lesion, risk factors, prediction.